Perancangan 7GHz Microwave Link Ujung Batu-Pasir Pengarayan - Nasution, Abdul Risyal; Rahayu, Yusnita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This paper proposed a reliable microwave backbone link design from Ujung Batu to Pasir Pengarayan by taking into account the antenna height and the distance. Pathloss 4.0 is used for designing microwave link and link budget analysis. A repeater is added between Ujung Batu to Pasir Pengarayan in order to improve the performance. This is due to an existing highland in between that affect to the antenna height. Mini link 7HC 128 QAM and Andrew antenna P8-6812 are used as microwave equipments. Design microwave links Ujung Batu- repeater and microwave link repeater â Pasir Pengarayan have availability 99.996%. Space diversity technique id used to improve the system as recommended by ITU-R G 826 of 99.999% availability.Keywords : Link budget, Space diversity, Availability, Pathloss 4.0